PERAN PEMBELAJARAN BAHASA DAN SASTRA INDONESIA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Abdul Rahman (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2018)
ABSTRACTIndonesia has an education figure that greatness is not inferior to other world education figures i.e. Ki Hajar Dewantara. He explained that education is an effort in increasing the growth of manners (inner strength, character, mind, and intellectualism) from the body of the students, so the live of the students suit their world. Learning is defined by Knowles as a way of organizing learners to achieve the goal. Manners operationally is a positive behavior that is done through the custom that is formed into a person's character/learners. Based on these two definitions appears that education, learning, character/characters is a unity that cannot be separated with each other. Positive behaviors that must be drilled to learners consists of many aspects and one of them is how to speak. Thus, training the speech containing positive behavior is mandatory for language teacher (Indonesian Language). Any language skills cannot be trained separately between one's skills with other language skills. As a professional teacher, arranging strategies for Indonesian language teacher which are always associated with character education will no longer be a burden. Literature is a picture of human life. Literature becomes right media in imparting a positive character for learners. Through the Indonesia language teacher professionalism will form a younger generation who have lofty manners or strong character. Keywords: learning, language and literature, characters.